Biodiesel/butanol blends as a pure biofuel excluding fossil fuels: Effects on diesel engine combustion, performance, and emission characteristics. (November 2020) - Huang, Yongcheng; Li, Yaoting; Luo, Kun; Wang, Jiyuan
Although both biodiesel and n -butanol are excellent renewable biofuels, most of the existing research works merely use them as the additives for petroleum diesel. As the main fuel properties of biodiesel and n -butanol are complementary, the biodiesel/ n -butanol blends are promising to be a pure biomass-based substitute for diesel fuel. In this paper, the application of the biodiesel/ n -butanol blends on an agricultural diesel engine was comprehensively investigated, in terms of the combustion, performance, and emission characteristics. First, the biodiesel/ n -butanol blends with 10%, 20%, and 30% n -butanol by weight were prepared and noted as BBu10 (10 wt% n -butanol + 90 wt% biodiesel), BBu20 (20 wt% n -butanol + 80 wt% biodiesel), and BBu30 (30 wt% n -butanol + 70 wt% biodiesel). It was found that adding 30 wt% n -butanol to biodiesel can reduce the viscosity by 39.3% and increase the latent heat of vaporization by 57.3%. Then the engine test results showed that with the addition of n -butanol to biodiesel, the peak values of the cylinder pressure and temperature of the biodiesel/ n -butanol blends were slightly decreased, the peak values of the pressure rise rate and heat release rate of the blends were increased, the fuel ignition was delayed, and the combustion duration was shortened. BBu20 has the approximate ignition characteristics with diesel fuel. Both the brake thermal efficiency and the brake-specific fuel consumption of BBu30 were increased by the average percentages of 2.7% and 14.9%, while NO x, soot, and CO emissions of BBu30 were reduced by the average percentages of 17.6%, 34.1%, and 15.4%, compared to biodiesel. The above variations became more evident as the n -butanol proportion increased.